The Role Of Customer Relationship Management In Improving Customer Experience: A Literature Review - Hasanah Kurniadewi (Dinasti Publisher, 2025)
This analysis aims to examine the role of CRM in increasing customer satisfaction and loyalty. The research method used in this study is a literature approach by collecting various sources that discuss the application of CRM in various company sectors. The results show that CRM can expand marketing, improve long-term relationships with customers, and facilitate product and service customization according to customer needs. Nonetheless, the main challenges faced are complex system integration and data quality that is not always accurate. Thus, effective CRM implementation requires not only sophisticated technology, but also a change in organizational culture and a commitment to focusing on customer satisfaction.